INTENSI MASYARAKAT DALAM MENYALURKAN ZAKAT, INFAQ, DAN SHADAQAH (ZIS) MELALUI PENGGUNAAN PLATFORM CROWDFUNDING - Bimmo Dwi Baskoro; Gina Destrianti Karmanto (Program Studi Manajemen Universitas Muslim Maros, 2020)
In Indonesia, the strategy of collecting zakat, infaq, and shodaqoh (ZIS) continues, one of which is through digital collection through the use of a crowdfunding platform. However, the community's intention or intention to distribute zakat, infaq, and shodaqoh through the crowdfunding platform has decreased based on the percentage of raising. The purpose of this study is to test the theory of Technology Acceptance Model (TAM) and Trust (Trust) by analyzing what factors influence the intention of the Indonesian people to distribute ZIS through the use of a crowdfunding platform. The population in this study are people who have used digital payment platforms with a sample size of 385 respondents. This study uses data analysis techniques with the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The results of this study indicate that individuals believe that crowdfunding platforms are very easy to use and learn. On the other hand, individuals have high confidence in the crowdfunding platform and have a high perception of usability for the crowdfunding platform. The individual intensity is very high for using the crowdfunding platform. In the SEM-PLS analysis results, it was found that perceived ease of use, perceived usefulness, and trust have a positive and significant effect on behavioral intention. In addition, perceived ease of use and trust have an indirect effect on behavioral intention. This research is expected to be able to provide benefits in relation to policies to increase behavioral intention to distribute zakat, infaq, and Shodaqoh through the use of crowdfunding platforms.